Faktor Status Kesehatan Ibu Hamil Terhadap Pemeriksaan ANC di RS Kartika Husada Setu Pada Bulan November Tahun 2024 - Gita Permata Sari; Elfira Sri Futriani (Jurnal Ners, 2025)
Antenatal care (ANC) visits are one of the important efforts in maintaining maternal and fetal health during pregnancy. However, various factors in the health status of pregnant women can affect compliance with ANC visits. This study aims to determine the characteristics of the health status of pregnant women related to the completeness of ANC visits. This study used an observational method with a cross-sectional approach. Researchers did not intervene, but only observed the variables studied. The target population was all pregnant women who underwent ANC examinations at the hospital directly or through referrals from first-level health facilities. A sample of 82 respondents was determined based on Dahlan's (2013) calculation formula for categorical data, with consecutive sampling techniques. Data were analyzed descriptively to see the relationship between maternal health status (age, pregnancy spacing, pregnancy history, medical history, and pregnancy status) with the completeness of ANC visits. The majority of pregnant women who were in the non-risk category (age 20–30 years, ideal pregnancy spacing, without a history of pregnancy or medical risk) showed high compliance with complete ANC visits. Conversely, mothers with risky pregnancy characteristics showed a lower level of ANC visits. The health status of pregnant women affects the regularity of ANC visits. Mothers with non-risk characteristics tend to be more compliant, while mothers with risky conditions need further attention and education to continue to make routine pregnancy visits.